Superconducting properties of MgB2 after reaction with silicon and carbon-containing additives - Tan, Kwee Yong (2011)
SiC is one of the promising dopants that effectively improves the critical current density (Jc) of MgB2 by substituting C into B-site and enhances electron scattering. However, the roles of Si and C in influencing the superconducting properties of MgB2 are not fully understood. Furthermore, systematic study on the optimum dopant addition level and effect of sintering temperature are required in order to provide further insight into how SiC or both Si and C enhance Jc. In this study, nano-SiC and combination of nano-Si and nano-C (Si+C) that made of similar ratio to that of SiC [up to 15 weight percentage (wt.%)] was reacted with Mg+B powder by in situ solid state method. These bulks were sintered at 650°C and 850°C, respectively. Characterizations are performed by using Xray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Magnetic Property Measurement System (MPMS). These samples were compared in terms of phase formation, lattice properties, microstructure and superconducting properties. At 650°C, samples reacted with SiC show smaller a-axis and more vigorous lattice distortion because of higher C substitution at B site as compared to same amount of (Si+C) addition. This is due to the reactive form of C atoms released from Mg-SiC reaction with lower Gibbs free energy. Higher C substitution in SiC reacted sample results in more severe degradation in superconducting transition temperature (Tc) arising from more severe lattice distortion. Samples reacted with SiC (up to 5 wt.%) show stronger improvement in Jc at both 5 K and 20 K mainly because of smaller grains that enhance grain boundary pinning and degraded crystallinity due to lattice defect. At 850°C, (Si+C) reacted samples have greater extent of a-axis contraction and more severe lattice distortion because of higher C substitution than those samples reacted with SiC. Such phenomenon is probably due to the availability of more C in which separate Si and C particles are used or effect of higher sintering temperature. Higher level of C substitution in (Si+C) reacted samples leads to more severe Tc suppression because of more severe lattice distortion. On the other hand, (Si+C) reacted samples show stronger Jc improvement at both 5 K and 20 K due to higher C substitution at B-site that further enhances electron scattering. As a conclusion, for sintering at 650°C, reaction of SiC with MgB2 is preferred while sintering at 850°C, reaction of (Si+C) with MgB2 is favored as higher C substitution and more lattice defects occur in these samples which effectively enhance the Jc. Among all samples, the Jc of 5 wt.% SiC reacted MgB2 at 650°C, as compared to the pure sample,is improved by a factor of two at 5 K for the applied field of 6 T and 60 % more at 20 K for the applied field of 4 T, respectively. This improvement is due to degraded crystallinity and higher C substitution that further scatter the electrons and smaller grains that enhance grain boundary pinning.